Plano de Gestão de Logística Sustentável (PLS): proposta de um modelo para a Prefeitura Municipal de Cachoeira do Sul/RS - Helbert, Gabriella Lisbôa (2019)
The study aimed to propose a sustainable management plan (PLS) for the Cachoeira do Sul City Hall, in order to assist in the execution of internal processes; services provided to citizens; Rationality of Exhibitors; not conscious consumption; and in the precise allocation of resources directed, thus, the municipality for sustainable development and generation of economy. At this juncture, the objectives are worthy of this work and know the theoretical assumptions about PLS; recognize the needs, aligned with the concept of sustainability; "The work is based on Normative Ruling No. 10/2012 (Brazil, 2012b), a law for the elaboration of the plan. In the same way, the study presented the following research problem: which the economic, social and environmental perspective in the elaboration of a PLS in the Municipality of Cachoeira do Sul? The methodology used, therefore, involved a case study with a prescriptive and qualitative approach. For that, a bibliographical research was conducted, which served as a guide for the composition of this study. Subsequently, a qualitative research was applied, using, as an instrument of data collection, individual semistructured interviews with managers of five Secretariats linked to the organization's logistical and sustainable processes, which are: Secretariat of Administration; Secretariat of Coordination and Planning; Secretary of Finance; Secretariat of Environment; and Secretary of Works. The guiding categories of the interviews were consumer material; electricity; water and sewage; selective collect; quality of life in the work environment; purchases and hirings; and staff turnover. In addition to the aforementioned researches, participant observation was used to complement the data collection, considering that the author acts within the organizational context under analysis. The results showed that, in general, the City Hall has few and isolated actions regarding the promotion and adoption of sustainable practices and these procedures are neither formalized nor standardized, varying from sectors and even Secretariats. It is evident, then, the real need to formalize the actions already carried out by the servers. Needs were also diagnosed as control over purchased consumer materials; use of sustainability criteria for purchases and contractions; preparation of a basic sanitation plan for the Municipality; correct segregation of waste; updating of the city's Master Plan. In this context, the proposal of a PLS for the Cachoeira do Sul City Hall, based on the results of this research. Was presented as an innovative planning instrument, in a way that allows to establish sustainability and rationalization practices in the management of the organization.